Assessing The Implementation of Computer Aided Facility Management (CAFM) In Malaysia Industry - Tuan Ibrahim, Tuan Nur Nasuha; Mariah Awang, (Progress in Engineering Application and Technology, 2022)
As a developing country gradually implementing Facilities Management in various public and commercial sectors, Malaysia will recognize the importance of Computer Aided Facility Management (CAFM) in the company, which will benefit this industry. The goal of this research is to determine the full use of computer-aided technology facility management industry and analyse the CAFM in Malaysian companies for FM services. While the industry's top companies play their roles in developing Facilities Management to be more mature and established throughout it, the importance of CAFM should not be overlooked because it helps drive the process of Facilities Management services to be more manageable and secure. Therefore, to obtain information this study used a quantitative method approach to analyse the data. The information gathered from respondents will be analysed using SPSS, Microsoft Excel, and a Google Form. Accordingly, to the result obtained, the effectiveness of using CAFM in the organization has an average mean score total is between 3.35 to 3.43 respectively. To summarize the implementation of CAFM in organizations is moderate and the result can be used for future research to ensure study can focus Facilities Management organisations in Malaysia providing the best CAFM system in comparison to European countries that were pioneers in the Facilities Management industry hence this research to promote best practice on CAFM aspect in Facilities Management industry.